Experiences of early labour management from perspectives of women, labour companions and health professionals: A systematic review of qualitative evidence. (February 2018) - Beake, RM, MA, Research Associate, Sarah; Chang, BA, MPhil, PhD, Lecturer, Yan-Shing; Cheyne, RM, RGN, MSc, PhD, Professor of Midwifery, Helen; Spiby, MPhil, RN, RM, Professor of Midwifery, Helen; Sandall. RM, MSc, PhD, Professor of Social Science and Women's Health, Jane; Bick, Debra
Abstract: Objectives: to examine evidence of women's, labour companions' and health professionals' experiences of management of early labour to consider how this could be enhanced to better reflect women's needs. Design: a systematic review of qualitative evidence. Setting and participants: women in early labour with term, low risk singleton pregnancies, not booked for a planned caesarean birth or post-dates induction of labour, their labour companions, and health professionals responsible for early labour care (e.g. midwives, nurse-midwives, obstetricians, family doctors). Studies from high and middle income country settings were considered. Findings: 21 publications were included from the UK, Ireland, Scandinavia, USA, Italy and New Zealand. Key findings included the impact of communication with health professionals (most usually midwives) on women's decision making; women wanting to be listened to by sympathetic midwives who could reassure that symptoms and signs of early labour were 'normal' and offer clear advice on what to do. Antenatal preparation which included realistic information on what to expect when labour commenced was important and appreciated by women and labour companions. Views of the optimal place for women to remain and allow early labour to progress differed and the perceived benefit of support and help offered by labour companions varied. Some were supportive and helped women to relax, while others were anxious and encouraged women to seek early admission to the planned place of birth. Web-based sources of information are increasingly used by women, with mixed views of the value of information accessed. Key conclusions and implications for practice: women, labour companions and health professionals find early labour difficult to manage well, with women unsure of how decisions about admission to their planned place of birth are taken. It is unclear why women are effectively left to manage this aspect of their labour with minimal guidance or support. Tailoring management to meet individual needs, with provision of effective communication could reassure women and facilitate timely admission from perspectives of women, their companions, midwives and other health professionals. Information on labour onset and progress, and approaches to pain management, should be shared with women's labour companions to enable them to feel more confident to better support women. Further research is needed of the impact of different models of care and increasing use of web-based information on women's approaches to self-management when labour commences. PROSPERO 2014 CRD 42014009745 Highlights: Women want effective communication in early labour from health professionals who offer clear advice in a sympathetic manner. Women require realistic information on what to expect and what early labour may feel like. Some labour companions were supportive of women remaining at home. Others supported early admission because they were anxious or unsure of their role. Further research is needed into interventions which could reduce women's anxiety when labour commences.